Modelos de fomento e P&D em farmacêuticos e benchmarking internacional - Rafael Pinho Senra de Morais (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Brazil has evolved strikingly in the last few years in the area of health assistance and access to medicines by its aging and urbanizing population. The government has also set the health industry - which includes pharmaceutical innovation - as one of its strategic sectors to be developed in the coming years through tailored policies. However, there is still improvement to be made in the area of matching innovation to the epidemiological needs of Brazilian population. This paper reviews the international literature on mechanism design to bring incentives to pharmaceutical innovation without compromising access to medicines at affordable prices to the broader population and then proposes some policies to be implemented by the Brazilian government in this area. A particular issue at stake is the use of the governmental purchasing power to induce innovation by private pharmaceutical companies, as recommended by some recent and incisive international literature and implemented through a couple of international initiatives these days.
Keywords: L65; L52; I18; O31; O34; 330; medicines; pharmaceutical R&D; incentives; pull mechanisms